Pelatihan Digitalisasi Koperasi pada KSPPS Surya Amanah Ummah Kabupaten Sleman, Yogyakarta - Hamdani, Dadan; Hidayat, Udin (LPPM Universitas Koperasi Indonesia, 2024)
Cooperative digitalization training at KSPPS Surya Amanah Ummah in Sleman Regency, Yogyakarta aims to increase the capacity and skills of cooperative members in adopting digital technology. KSPPS Surya Amanah Ummah as a sharia-based financial institution is faced with the challenge of improving operational efficiency and service to members through the application of information technology. This training is designed to provide practical understanding and skills in the use of digital financial software, data management and marketing strategies online. The training method involves direct practical sessions and theoretical explanations integrated with case studies from cooperatives that have successfully implemented digitalization. The training participants consisted of administrators and members of KSPPS Surya Amanah Ummah who were interested in expanding their insight and skills in utilizing technology to increase the competitiveness of cooperatives. It is hoped that the results of this training can increase the operational efficiency of KSPPS Surya Amanah Ummah, expand service accessibility to cooperative members, and increase understanding of the benefits and challenges of digitalization in the context of sharia cooperatives. Thus, this training not only supports the growth of KSPPS Surya Amanah Ummah internally, but also contributes to local economic development through improving the performance and sustainability of cooperatives. Cooperative digitalization training at KSPPS Surya Amanah Ummah is the right step in facing the increasingly growing era of digitalization. With digitalization, cooperatives can increase operational efficiency, provide better services to members, and compete in an increasingly competitive market. Therefore, it is important for cooperatives to continue to follow technological developments and carry out comprehensive digital transformation.